Understanding Secularism and National Identity in French Political Discourses - Aprillia Firmonasari; Wening Udasmoro; Yohanes Tri Mastoyo (Humaniora, 2020)
The concept of secularism or laicité is expressed in political discourses in various ways by the French presidential candidates in the 2017 campaign. Both candidates, Emmanuel Macron (EM) and Marine Le Pen (MLP) used specific forms and lingual expressions to explain secularism and national identity, especially those related to ‘Islam’, ‘immigration’ and ‘terrorism’. This study uses critical discourse analysis linked to their parties’ ideologies based on identity, activities, goals, norms, and values. In the discourses presented by EM and MLP, Islam is associated with religion, Muslims, jihad, Islamic fundamentalists, the burqa, and secularism. The results of discourse analysis show that EM’s and MLP’s discourses on secularism and Islam are notably different. MLP views secularism in France as being under threat due to external threats, namely immigrants and in particular Muslim immigrants. In contrast, EM views secularism as a concept to support and protect the identity of the nation and to support and to add to the diversity of French culture and identity. The findings of this research is that French concepts of national identities, which is closely related to secularism, correlates to the ideologies of the respective presidential candidates’ parties. The relationships between the parties’ ideologies, national identities, and discourses investigated in this research can be used as a methodology for political discourses, especially French political discourses.